Determinants of Innovativeness in Manufacturing Small and Medium Enterprises in Kenya: Unpacking Entrepreneurial Orientation - Mkalama, Ben; Ndemo, E. Bitange; Maalu, Jackson; Pokhariyal, Ganesh (Archives of Business Research, 2021)
In spite of firm innovativeness being identified as essential for growth, there exists a dearth of studies that relate entrepreneurial orientation and innovativeness in manufacturing small and medium enterprises in the developing world. In this article, we unpack the dimensions of entrepreneurial orientation and examine their influence on innovativeness of manufacturing small and medium manufacturing enterprises. This was a cross sectional survey with a stratified sample size of 363 firms. Regression models were used to validate the derived hypothesis. We discuss the implications of the results which show that the dimensions were individually not found to have a significant effect on innovation but yet entrepreneurial orientation had an influence on firm innovativeness. We identify the need for additional studies to broaden the scope of future studies across several geographies. We conclude by challenging the ever-dynamic local institutional policies that have not had a significant impact on the effect of entrepreneurial orientation on innovativeness of SMEs across many developing countries.